The cult of order: in search of underlying patterns of the colonial and neo-colonial "grammar of educationalisation" in the Belgian Congo. Exported school rituals and routines?. (4th March 2017) - Van Ruyskensvelde, Sarah; Hulstaert, Karen; Depaepe, Marc
Abstract: An analysis of the history of primary education in Belgium by Depaepe et al. in 2000 has demonstrated how the idea of "order" structured classroom reality in the course of the nineteenth and twentieth centuries. This "order" is not only visible in the internal organisation of schooling (e.g. division into year classes, a structured timetable, the use of the didactics of teacher-centred instruction), but also in the design of the curriculum. Good behaviour and moral decency were consistently prioritised over "intellectual knowledge". Very similar paternalising practices – including the cult of order – were transported to the Belgian colony. The implementation of these practices, however, did not go smoothly, because the African context of missionary education was totally different from the Belgian educational context. Precisely as a result of these difficulties, the core characteristics and likewise mistakes of the transported "grammar of educationalisation" become even more apparent. On the basis of a variety of sources, this paper demonstrates that secondary education for boys in the Belgian colony of Congo was founded on the same educational norms and values that characterised nineteenth-century Belgian education. In this respect, order was considered the conditio sine qua non for discipline and self-discipline. But, in contrast to what Nikolas Rose has argued, the Foucaultian paradigm – although attractive and interesting – is not imperative in explaining the educational strategy of order. On the contrary, the development of the history of education as a science could benefit from a theoretical framework coming "from within" the discipline. Until today, the history of educational practice has been explained from a history of education perspective only to a limited extent. By exploring the duality of a didactic grammar of schooling, on the one hand, and an educational semantics of moralisation, on the other hand, this paper contributes to the development of a theoretical framework from within the history of education.